Major and trace elements composition of tidal flat sediment around Sungai Tengi Estuary, Tanjung Karang Selangor - Sahibin Abd. Rahim,; Mohamad Md. Tan,; Ramlan Omar, (Universiti Kebangsaan Malaysia, 2004)
Eleven marine sediment samples from Sg. Tengi Estuary, Tanjung Karang were analysed for their major elements in the oxides form (SiO2, Al2O3, Fe2O3, Na2O3, MgO, CaO, K2O, TiO2, P2O5 and MnO) and trace elements (Ba, Co, Cr, Cu, Ni, Pb, Rb, Sr, V, Zn, and Zr) contents. The muddy marine sediment was collected at the left and right side of the river mouth as far as one kilometre away and about 25-30 meters from the edge of existing growth. Some of the mud sample appears to have cockleshell flakes in them. The mean of major elemental content (oxides form) in the sediment in decreasing order were dominated by SiO2 (56.3%), followed by Al2O3, (15.5%), Fe2O3 (4.1%), Na2O (2.7%), CaO (2.6%), MgO (2.3%), K2O (1.8%), TiO2 (0.5%), P2O5 (0.14%) and MnO (0.06%). Volatile substances represented by loss on ignition (LOI) (13.9%) occupied substantial amounts of the sediment volume. The most abundant trace elements displayed as mean was Zr (222 mgkg-1), followed by Ba (200 mgkg-1), Sr (172 mgkg-1), Rb (131 mgkg-1), Zn (103 mgkg-1), V (l02mgkg-1), Cr (84 mgkg-1), Pb (40 mgkg-1), Ni (34 mgkg-1), Cu (31 mgkg-1) and Co (22 mgkg-1). Correlation analysis showed that Cr, Pb and Zn were positively related to the Fe203 and Al2O3 content whereas increase in pH immobilised Cr and Zn in the sediment. The mean of Cr (84 mgkg-1) and Zn (103 mgkg-1) content in sediment were higher than the lower limit of their respective threshold concentration.